2007
DOI: 10.1128/aem.01222-07
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cultivated Endophytic Bacteria from Sugarcane: Genetic and Biochemical Characterization of Burkholderia cepacia Complex Isolates

Abstract: Bacteria were isolated from the rhizosphere and from inside the roots and stems of sugarcane plants grown in the field in Brazil. Endophytic bacteria were found in both the roots and the stems of sugarcane plants, with a significantly higher density in the roots. Many of the cultivated endophytic bacteria were shown to produce the plant growth hormone indoleacetic acid, and this trait was more frequently found among bacteria from the stem. 16S rRNA gene sequence analysis revealed that the selected isolates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
114
0
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(161 citation statements)
references
References 80 publications
(65 reference statements)
17
114
0
24
Order By: Relevance
“…Bacteria were isolated from the rhizosphere according to the methodology proposed by Mendes et al (2007), whereby 1 g of soil adhered to the roots was incubated for one hour under agitation at 130 rpm, at room temperature, in 100 mL of phosphate buffer (20 mM, pH 7.4). After agitation, the material was serially diluted and concentrations of 10 -8 , 10 -9 and 10 -10 were plated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria were isolated from the rhizosphere according to the methodology proposed by Mendes et al (2007), whereby 1 g of soil adhered to the roots was incubated for one hour under agitation at 130 rpm, at room temperature, in 100 mL of phosphate buffer (20 mM, pH 7.4). After agitation, the material was serially diluted and concentrations of 10 -8 , 10 -9 and 10 -10 were plated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on isolation and selection of isolates in different plant species have demonstrated that the ability of some bacteria to produce plant growth-promoting substances may be highly specific to certain plant species or even cultivars, as well as to the different environments where they are inserted, or even affected by the stress imposed on the microbial community due to environmental and anthropogenic alterations (Mendes et al, 2007;Oliveira et al, 2009;Jha et al, 2009b;Prakamhang et al, 2009). In this work, it was further verified that such ability may be related to the cultivation time and the combination of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the isolates recovered from in vitro yacon cultures were endophytes except for F. oryzihabitans, which grew endo and epiphytically. Several reports indicate that plant growth promoting bacteria are beneficial endophytes growing in association with the host [21][22][23]. Among the S. sonchifolius isolates, Microbacterium imperiali and Sphingomonas paucimobilis were the highest IAA producers ( Table 4).…”
Section: Isolation and Identification Of Epiphytic And Endophytic Bacmentioning
confidence: 99%